Eco-innovation and firm performance in European highly energy consumers and polluting sectors - Madaleno, M.; Robaina, M.; Dias, M. F.; Meireles, M. (2020 17th International Conference on the European Energy Market (EEM), 2020)
This study investigates the effect of eco-innovation actions on firm performance, considering both turnover and employment growth, in European enterprises, focusing on the highly energy consumer sectors and the most polluting ones. The total sample includes 44647 firms from 13 different European Union countries and is based in the most recently released Community Innovation Survey (CIS). Using cross-section econometric techniques, results showed that eco-innovations might affect positively turnover growth, as well as employment growth. Both human capital and the number of adopted eco-innovation strategies influence positively the firm performance. Eco-innovation behavior is also found to be more important than non-eco-innovation in determining firm performance. Moreover, the positive impacts of eco-innovation in firms could be leveraged by the government financial support in these sectors. The conclusions presented showed that eco-innovations are an opportunity for companies cost reduction, opening doors to new growth possibilities.